Beyond transitional justice: transformative justice and the state of the field (or non-field) - Evans, Matthew (Directions and development in criminal justice and law, 2022)
In, against, and beyond transitional justice : themes and dilemmas for the field (or non-field) / Matthew Evans -- The uses of transitional justice as a field / Maja Davidovic -- Crisis, faith, and transformation in transitional justice / Dustin N. Sharp -- Beyond disciplines, beyond fields, beyond transitional justice / Matthew Evans -- Foregrounding transitional justice success through the development of thin sympathy / Joanna R. Quinn -- 'Greening' transitional justice / Rachel Killean and Lauren Dempster -- Transforming experiences of citizen security? / Dáire McGill -- What role for social scientific research in transformative justice? / Eric Hoddy -- Transitional justice : understanding the field / Christine Bell.